2009
DOI: 10.1093/nar/gkp770
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the EndoG/EndoGI complex: mechanism of EndoG inhibition

Abstract: EndoG is a ubiquitous nuclease that is translocated into the nucleus during apoptosis to participate in DNA degradation. The enzyme cleaves double- and single-stranded DNA and RNA. Related nucleases are found in eukaryotes and prokaryotes, which have evolved sophisticated mechanisms for genome protection against self-antagonizing nuclease activity. Common mechanisms of inhibition are secretion, sequestration into a separate cellular compartment or by binding to protein inhibitors. Although EndoG is silenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 45 publications
2
48
0
Order By: Relevance
“…The active site of Smn, NucA and Vvn is also very similar to those of apoptotic endonuclease G from Drosophila melanogaster (Dm-endoG), [16] the His-Cys box homing endonuclease, I-PpoI, from the slime mould Physarum polycephalum, [17][18][19] the DNA-entry nuclease EndA from Streptococcus pneumoniae, [20] and a recently identified endonuclease from the protozoan parasite Leishmania infantum (Li-endoG) [21] (Figure S1 in the Supporting Information). Moreover, cleavage experiments with deoxythymidine 3',5'-bis-(p-nitrophenylphosphate) as an artificial minimal substrate have indeed shown that Smn, NucA and I-PpoI follow the same mechanism of phosphodiester bond hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…The active site of Smn, NucA and Vvn is also very similar to those of apoptotic endonuclease G from Drosophila melanogaster (Dm-endoG), [16] the His-Cys box homing endonuclease, I-PpoI, from the slime mould Physarum polycephalum, [17][18][19] the DNA-entry nuclease EndA from Streptococcus pneumoniae, [20] and a recently identified endonuclease from the protozoan parasite Leishmania infantum (Li-endoG) [21] (Figure S1 in the Supporting Information). Moreover, cleavage experiments with deoxythymidine 3',5'-bis-(p-nitrophenylphosphate) as an artificial minimal substrate have indeed shown that Smn, NucA and I-PpoI follow the same mechanism of phosphodiester bond hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an inhibitor of EndoG (EndoGI) was found in the D. melanogaster gene cg4930 which consists of 2 homologous domains, each of them able to bind one EndoG nuclease (Temme et al, 2009). The crystal structure of the complex was resolved which supported the 2:1 stoichiometry (Loll et al, 2009). The group proposed a life insurance function for EndoGI for leakage of mitochondria by release of EndoGI from the nucleus and binding EndoG in the cytosol.…”
Section: Role Of Endonuclease G In Cell Death and Diseasementioning
confidence: 71%
“…4a shows two molecules of the Drosophila nuclease EndoG in complex with the inhibitor EndoGI 41 . EndoGI consists of repeated domains separated by a disordered linker that allows them to wrap around both sides of the EndoG homodimer, binding each EndoG subunit in a very similar manner.…”
Section: Resultsmentioning
confidence: 99%